Tacos - Golkar, Golriz (2019)
"This book introduces readers to the history and culture associated with tacos, and it shows them they can make this favorite food at home. Vivid photographs and easy-to-read text aid comprehension for early readers. Features include a table of contents, an infographic, fun facts, Making Connections questions, a glossary, and an index. QR Codes in the book give readers access to book-specific resources to further their learning.
A Mexican favorite -- Tacos in America -- Tacos everywhere -- How to make tacos.
Includes index.
Ages 4-8
Keywords: Tacos -- Juvenile literature; Junk food -- Juvenile literature; Junk food; Tacos; Juvenile works